Rome - Balchin, Paul N., author.
1 online resource (x, 374 pages)
Keywords: First published in 2017, Rome: The Shaping of Three Capitals explores the impact of political history on the built environment of the Eternal City. The book divides Rome's history into three main periods: the rulership of the early kings from the 8th to the 6th centuries BC; the period of Etruscan culture and architecture up to the end of the Roman Empire in 5th century AD; and, the 6th century to 1870, when Rome stood as the ecclesiastical capital of the Catholic Church and the temporal state of the Papal States. The final section of the book examines the Risorgimento, the unification of Italy, and the development of the fascist state; a time when Rome became the capital of Italy and endeavoured to establish a new empire. Exploring political instability and change, Balchin demonstrates the strong connection between politics and the physical shaping of the city through an examination of the successive styles of architecture, from Classical to Modernist.